The Daily life of the Crimean Murzas in the intellectual heritage and personal book collection of Ismail Gasprinsky - S. A. Seitmemetova (Вестник Майкопского государственного технологического университета)
Introduction. Currently, scientific interest in the representatives of the Crimean Tatar noble class has increased, and more and more attention is being paid to the topic of the daily life of the Muslim elite of Crimea in different periods of time. The range of issues studied in the article is an unexplored aspect in the history of the Taurida province in the late 19th and early 20th centuries. The article examines the Murz estate of Crimea in the late 19th and early 20th centuries through the eyes of its contemporary, Ismail Bey Gasprinsky, a reformist teacher and publisher who had a significant impact on the development of culture, education and public life of the majority of the Turkic-Muslim peoples of the Russian Empire. The goal of the research is to explore those aspects of social and private life of this class that most comprehensively inform about their hobbies, interests and lifestyle in general. It is these components that are vivid expressions of the spirit of the era and help to better understand the peculiarities of the daily life of representatives of noble Crimean Tatar families.The Materials and Methods. General scientific methods of analysis and synthesis, comparative historical and problem-chronological methods have been used in the research. The research is based on unpublished sources, such as articles from the newspaper Terjiman, as well as books stored in the Bakhchisarai Museum-Reserve.The Results. In accordance with the principles of historicism and objectivity, the author was the first to introduce previously unpublished sources on the history of the Crimean Tatar nobility into scientific circulation.Discussion and Conclusion. The social life of the Crimean Murz have been examined: attending official events, participating in agricultural exhibitions, charity events. The leisure time of the Crimean Tatar elite, wedding celebrations and entertainment have been considered. It’s been concluded that the intellectual heritage of the enlightener I. Gasprinsky is not only a valuable source on the history of the formation and development of national periodicals and the education system of the Turkic-Muslim population of the Russian Empire in the late 19th and early 20th centuries, but also provides insight into the virtually unexplored world of daily life in the Crimean Murz.